Microwave Heating Characteristics of Emulsified Asphalt Repair Materials Incorporated with Steel Slag - Yongfeng Wei; Jinyang Huo; Zhenjun Wang; Jiangtao Gao (Advances in Materials Science and Engineering)
Emulsified asphalt needs to be cured for a certain age after demulsification to produce strength, which seriously affects the traffic opening time. In this work, microwave heating technology was applied for emulsified asphalt repair materials. Steel slag with high microwave activity was adopted to improve the performance of emulsified asphalt repair materials by microwave heating. Effects of steel slag sizes and contents on the heating rate, temperature distribution, and thermal performance of emulsified asphalt repair materials were analyzed by close microwave heating, open microwave heating, and repair simulation tests. Results show that the temperature of emulsified asphalt repair materials presents three different heating stages under microwave irradiation. The “critical point of phase transition” in the three stages is gradually advanced with the increase in steel slag content. The core temperature and maximum temperature of emulsified asphalt repair materials with different steel slag sizes are basically the same; however, the heat distribution of emulsified asphalt repair materials is significantly different. In contrast to conventional asphalt mixture, there exists a smaller temperature difference. The temperature of repairing materials can reach above 80°C. The interface area can form an embedded interface structure. Incorporation of steel slag and adoption of microwave heating are effective to improve the performance of emulsified asphalt repair materials.